2018
DOI: 10.1186/s40001-018-0320-2
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 combined with trimetazidine in the prevention of contrast-induced nephropathy in patients with coronary heart disease complicated with renal dysfunction undergoing elective cardiac catheterization: a randomized control study and in vivo study

Abstract: BackgroundContrast-induced nephropathy (CIN) is one of the common hospital-acquired acute renal failures. The purpose of this study was to investigate whether Coenzyme Q10 (CoQ10) and trimetazidine (TMZ) can prevent the occurrence of CIN after elective cardiac catheterization in patients with coronary artery disease complicated with renal dysfunction.MethodsConsecutive coronary artery disease patients with renal insufficiency scheduled for coronary angiography were enrolled in randomized, paralleled, double-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
(30 reference statements)
2
16
0
Order By: Relevance
“…Corroborating with the findings of Chen et al that demonstrated the protective effect of CoQ10 in combination with trimetazidine against CI-AKI in patients with coronary heart disease complicated with renal dysfunction as well as on rat models of CI-AKI, the results of this study have demonstrated the renoprotection of CoQ10 in an experimental model of risk factor of DM for CI-AKI [ 42 ]. In the present study, CoQ10 presented an antioxidant effect on the CI-AKI in male diabetic rats by improving renal function and renal hemodynamics, preserving morphology and reducing oxidative stress.…”
Section: Discussionsupporting
confidence: 84%
“…Corroborating with the findings of Chen et al that demonstrated the protective effect of CoQ10 in combination with trimetazidine against CI-AKI in patients with coronary heart disease complicated with renal dysfunction as well as on rat models of CI-AKI, the results of this study have demonstrated the renoprotection of CoQ10 in an experimental model of risk factor of DM for CI-AKI [ 42 ]. In the present study, CoQ10 presented an antioxidant effect on the CI-AKI in male diabetic rats by improving renal function and renal hemodynamics, preserving morphology and reducing oxidative stress.…”
Section: Discussionsupporting
confidence: 84%
“…Despite the availability of hyaluronidases, it has being discussed whether all HA fillers are sensitive to the activity of these enzymes; in fact, several studies have shown that the resistance to degradation depends on numerous factors, such as the concentration of HA, the type and degree of cross-linking, and the cohesive properties [2326].…”
Section: Introductionmentioning
confidence: 99%
“…Five studies were then excluded for the following reasons: full-text not available, 20 study results not yet published, 21 patients did not undergo PCI 22 and outcomes not relevant. 23,24 Fifteen trials 10,12,13,15,[25][26][27][28][29][30][31][32][33][34][35] were included in the systematic review and 14 trials in the meta-analysis. Data were not available as mean and standard deviation from one study and hence it was not included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%